The Effect of (Think - Pair – Share) Strategy on Performing Some Volleyball Fundamental Skills in Second Grade Secondary School Students - Jebbar, Mohammed; Hekmat, Assmaa (Journal of Physical Education, 2020)
The research aimed at designing exercises according to think – pair and share strategy in fundamental skills in volleyball as well as identifying the effect of this strategy on some fundamental volleyball skills performance in second-grade secondary school students. The researchers used the experimental method on second-grade secondary school students to conclude significant differences between pre and posttests in the subjects of the research as well as significant differences in posttests in favor of the experimental group. Finally, they recommended using think – pair and share strategy for developing the performance of some basic skills in volleyball.